Patients' experience in Hong Kong hospitals: A comparison between south Asian and Chinese people - Nimisha Vandan; Janet Wong; Paul Yip; Daniel Fong (The Beryl Institute, 2020)
Patient experience in hospital is positively associated with both self-rated and objectively measured health outcomes. In many countries ethnic minority patients have more negative experience and bear a disproportionate burden of disease than their majority counterparts. However, hospital experience of ethnic minority patients in Asia is still unexplored. We aimed to explore the hospital experience of South Asian ethnic minority and compare that with local Chinese patients' experience in Hong Kong. A cross-sectional study sample comprised of 783 participants (388 South Asian and 395 Chinese). Picker Patient Experience-15 (PPE-15) questionnaire was used for data collection. Simple and multiple regressions were used to compare South Asian and Chinese participants' in-hospital stays. The regression analyses were done before and after adjusting for demographics and after Propensity Score Weighting (PSW). All estimates were accompanied by a 95% confidence interval. Two-sided tests were conducted with a significance concluded by a p-value. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.